Implementation of Tri Hita Karana Philosophy in Building Trust and Loyalty among Multicultural Consumers: : A Case Study of CV Liss Jaya Construction in Bali - I kadek Yona Adi Christian; Aditya Narendra Wardhana (Amkop Management Accounting Review (AMAR), 2026)
Purpose – This study aims to analyze the implementation of Tri Hita Karana, a traditional Balinese philosophy, in fostering trust and loyalty among multicultural consumers at CV Liss Jaya Construction in Bali. It explores how indigenous values can be integrated into business management within a diverse socio-cultural context. Design/methodology/approach – A qualitative research design with a narrative approach was employed to capture the depth of construction service management practices in Bali. Data were gathered through in-depth interviews, field observations, and source triangulation involving key informants (business owners), family members, employees, and multicultural consumers. The data were then analyzed using inductive thematic analysis. Findings – The results demonstrate that the Tri Hita Karana values are deeply internalized within the company’s business operations. The Parahyangan (harmony with God) dimension is manifested through spiritual practices and moral accountability. The Pawongan (harmony among people) dimension is realized through family-oriented leadership and transparent communication. Finally, the Palemahan (harmony with nature) dimension is reflected in environmental stewardship. The integration of these three pillars plays a vital role in building cross-cultural consumer trust, which subsequently evolves into relational loyalty and ensures the long-term sustainability of the construction business in Bali’s competitive market. Originality/value – This research provides unique insights into "Indigenous Management," demonstrating how local wisdom can effectively bridge cultural gaps and serve as a strategic tool for relationship marketing in a globalized business environment.